Model High Scope Solusi Meningkatkan Kemampuan Berkomunikasi Anak Usia Dini - Domingus Lero Bili; Lidia Vera Bessu; Triwanti Natara (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Communicating from an early age is the right first step in developing good language skills in children. Difficulty in communication can hinder a person from expressing ideas, thoughts, and opinions, which prevents good interaction between children, parents, teachers, and society in general. Good communication is built starting from parent-child, teacher-child, and parent-teacher collaborations to observe each child's development. This is because young children are very sensitive to stimuli in various aspects such as physical motor skills, cognitive, social-emotional, and language. This research aims to provide an overview of the application of the High Scope model in the communication skills of early childhood. This type of research is qualitative descriptive research. The use of qualitative research aims to understand the phenomenon and provide a clear picture of the implementation of the high scope model in early childhood education learning. Data were obtained through observation and documentation methods. The research results indicate that the communication skills of early childhood children in the implementation of the High Scope model are in the very good development category (BSB) and in the expected development category (BSH). This research implies an increase in the communication skills of early childhood children, making it important for teachers to develop this High Scope model in the development of every aspect possessed by early childhood children.